PEMAKNAAN NILAI MORAL DALAM FILM PARASITE - Andriani, Bella; Abidin, Sholihul (LPPM Universitas Putera Batam, 2020)
As a form of mass media, movie can also depicts reality as well as putting new values to the society. Parasite is a movie that promote moral values that applicable to the everyday life. In every scenes shown in this movie, it is believed the writers of the movie wanted to deliver meanings and also values to the audience. This research is about what moral values there are in the movie using roland barthes’s semiotik analysis theory to describe the values in symbols that shown in the movie. There are so many lessons and meanings that made the audience intrigued and learned about the values of life in every scenes of the movie. The result shows values about relationship with ourselves and with each other. Presumably, the values presented can be used as a lesson to be positive about daily life and deeper knowing about good values. Based on the description above, the writer is interested to do a research focused on the verbal messages shown in the parasite movie.